First encounters: Estimating the initial magnitude of attentional capture - Adam, Kirsten C. S.; Yang, Zi; Serences, John T. (Visual cognition, 2024)
Salient but irrelevant information often captures our attention. To quantify attentional capture in the lab, participants typically complete dozens or hundreds of trials that contain salient distractors. However, presenting distractors frequently may also incidentally introduce a secondary task-set to resist distraction. In everyday life, we typically encounter distractions once, not dozens of times, creating a disconnect between capture in the lab and in the world. Here, we had a simple but important question: how large is capture when participants encounter a salient distractor for the very first time? We used a larger-than-typical sample size combined with a single capture trial (Exp 1 N = 970, Exp 2 N = 1,025), and found that initial capture was ∼9x-15x larger than the average size of capture in typical laboratory tasks (∼370-580 ms). We also found evidence that initial capture was modulated by long- and short-term stimulus history, consistent with emerging theories about how history shapes attention. Our results suggest that participants are surprisingly successful at ignoring distractors in the lab, and that "one-shot" estimates may better reflect the full cost of capture by salient distractors.